Enhancing the innovativeness of local production systems - Polish experiences - Mariusz E. Sokolowicz; Aleksandra Nowakowska; Zbigniew Przygodzki (European Regional Science Association (ERSA), 2014)
Interest in territorial forms of organisation of production is currently at its peak, both among researchers striving to describe and explain various phenomena and among practitioners - representatives of authorities, entrepreneurs or experts involved in developing the idea. On this basis, the concept of so called local production systems (LPS) is being more and more popular among regional scientists as well as regional and industrial policy makers. LPS are usually defined as systems of businesses centred in geographical proximity around one core industrial activity, maintaining relations among themselves and with their territorial socio-cultural environment, and are considered as one of the key territorial form of organization of production, which can efficiently contribute to the regional development and regional innovativeness. Among policy makers of most of the European countries, local production systems are usually considered as conceptual equivalent of the notion of cluster, while the latter, together with cluster supporting policy, is treated as of one the most important forms of enhancing the innovativeness of economies on the local and regional level. Also in the case of Poland, clusters as a form of local production systems, represent a very important part of the economy, triggering endogenous development potential. However, the level of innovativeness of Polish clusters is a difficult subject to clear assessment. Innovation commitment of clusters in Poland largely varies and depends mainly on the structure of their membership, development stage, industry and regions of activity. However, for the last 5 years Polish cluster supporting policy has developed a valuable tool for monitoring the situation in this area, which is benchmarking of clusters. The aim of the paper is to present the level of innovativeness of Polish local production systems, based on the benchmarking results', with the emphasis of the dynamic aspect of this phenomena. Together with the review of the instruments of supporting innovativeness of LPS in Poland, these results gives an answer about both positive trends concerning the innovativeness of Polish economy and negative aspects, listed as main challenges and dilemmas of Polish regional policy for the next years.
Keywords: O25; O; 31; R10; 330; local production systems; regional innovativeness; regional innovation policy; benchmarking